2021
DOI: 10.1021/acssuschemeng.1c02323
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Hydration Kinetics of High Ferrite Cement: Synergic Effect of Gypsum and C3S–C4AF Systems

Abstract: High ferrite cement (HFC) has attracted widespread attention due to the low carbon footprint and energy consumption. Gypsum, one of the essential components in Portland cement, plays a crucial role in the performance development of the matrix. However, the effect of gypsum on the performance evolution of HFC is obscure and unpredictable owing to the transformation of mineral phase composition including C 4 AF and C 3 S. Understanding the effect of gypsum is of great significance to further optimize the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…After sufficient dissolution, NaOH solution (3 mol/L) was added to a beaker at a constant rate, and the pH was measured repeatedly using a pH meter (model: PHS-3C) until the pH of the solution was maintained at 12. The above series of operations were completed in a magnetic stirring water bath at different temperatures (5,25,50,70, 90 °C) and followed the same rules. Afterward, the mixture was sealed in glass bottles and stored in a constant temperature incubator at different temperatures (5, 25, 50, 70, 90 °C) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sufficient dissolution, NaOH solution (3 mol/L) was added to a beaker at a constant rate, and the pH was measured repeatedly using a pH meter (model: PHS-3C) until the pH of the solution was maintained at 12. The above series of operations were completed in a magnetic stirring water bath at different temperatures (5,25,50,70, 90 °C) and followed the same rules. Afterward, the mixture was sealed in glass bottles and stored in a constant temperature incubator at different temperatures (5, 25, 50, 70, 90 °C) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…In CSA cement, hydration of Fecontaining minerals (e.g., C 4 A 3−x F x $ and Ca 2 Fe 2−x Al x O 5 ) is the main source of the FH 3 phase, and it has been reported that the proportion of the ferric phase (Ca 2 Fe 2−x Al x O 5 , with C 4 AF being the typical one) in FR-CSA cement ranges from about 15 to 30%, and this proportion varies with the Fe/Al ratio. 25,26 C 4 AF has good cementitious properties and contributes well to the long-term strength of the cement, and increasing the C 4 AF content offers further potential for improvement in the properties of CSA cements. 26 Hydration of C 4 AF individually produces C 3 (A,F)H 6 or C 3 AH 6 and ferric hydroxide (FH 3 ) (eqs 3, 4), and, in the presence of gypsum, it produces ettringite and FH 3 (eq 5).…”
Section: Introductionmentioning
confidence: 99%
“…The initial water molecule was placed over the most active oxygen atom most accessible site to gain electrons and the most favorable for dissociative adsorption. [49][50][51] The adsorption energy (Δ𝐸) was calculated as follows Δ𝐸 = 𝐸 sys − 𝐸 ad − 𝐸 sur (2) where 𝐸 sys is the energy of the adsorbed system (eV), Δ𝐸 ad is the energy of the adsorbed molecules (eV), and 𝐸 sur is the energy of the surface (eV). A negative Δ𝐸 means that the adsorption is energetically favorable.…”
Section: The Adsorption Surface Determination and The Adsorption Ener...mentioning
confidence: 99%
“…Fe-rich Portland cement has been applied to reduce carbon emission and enhance sulfate resistance, which was composed of less C 3 A (0-2 wt.%) and higher C 4 AF (18-22 wt.%) than ordinary Portland cement (4-10 wt.% and 8-15 wt.% respectively), and it has attracted much attention in cleaner cement production. [2][3][4][5][6][7][8][9] C 4 AF and C 3 A determine the setting, workability, early and late strength, and durability of cement, and calcium sulfate (CaSO 4 ) is added to retard the hydration of C 4 AF and C 3 A, which avoids flash set and optimizes the strength development by avoiding a superimposed reaction between C 3 S and C 4 AF/C 3 A. 10 CaSO 4 also accelerated C 3 S hydration and enhanced the strength development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation